Automation of blood component preparation from whole blood collections. Issue 1 (22nd January 2014) - Cid, J.; Magnano, L.; Lozano, M.
<x xml:space="preserve">Abstract</x> Background and objectives Automation of blood component preparation (BCP) from whole blood (WB) collections is increasingly being widespread implemented. This review summarizes the quality of blood components obtained with new automated devices. Materials and methods We reviewed available literature on the quality of blood components obtained with new automated devices developed in the 2000s. Results Blood components obtained with the new devices met European standards. Of note, compared with platelet concentrates obtained with manual methods, automation of BCP improved the consistency of the final products. Conclusion The complete automation of BCP from WB collections is still in development and it represents a huge change in paradigm.